Towards the Development of DNA Vaccine Against Newcastle Disease Virus - Loke, Chui Fung (2002)
The etiological agent of Newcastle disease, Newcastle disease virus (NDV), a member of the family Paramyxoviridae and the genus of Rubulavirus, can cause up to 100% morbidity and mortality. Immune responses to both the fusion (F) and haemagglutinin-neuraminidase (HN) protein antigens of NDV were demonstrated to play an important role in the prevention of infection. Towards development of DNA vaccine, both the F and HN genes of a Malaysian heat resistant viscerotropicvelogenic NDV strain AF2240 were amplified and cloned into a mammalian expression vector, pEGFP-Ns, and expressed in a mammalian cell line under the control of the immediate early promoter of human cytomegalovirus. Six recombinant plasmids were constructed, namely pEGFP-N3/F, -N1/HN, - N3/HN-GFP, -N2/Fkoz, -N2/HNkoz and -N1/Fkoz-GFP with the later three constructs introduced with the kozak translation initiation sequences. Transient expression of F and HN proteins was assayed in vitro in Vero cell at 48 h posttransfection by indirect immunofluorescence using NDV polyclonal antibody and fluorescein isothiocyanate (FITC)-labelled anti-chicken IgG. The results showed that all the DNA-transfected cells exhibited bright cytoplasmic fluorescene, indicating both the F and HN proteins were successfully expressed in the mammalian cell line. Immunoblot analysis of the transfected cell lysates further verified the presence of the recombinant proteins with a distinct band of 64 kDa which corresponds to the uncleaved precusor Fo glycoprotein of NDV and two bands of -62 and 72 kDa as unglycosylated and glycosylated HN glycoproteins, respectively. eSS]-methionine pulsed labelling of transfected cells confirmed the expression of green fluorescent protein (GFP)-fusion protein of F, but not HN-GFP. DNA inoculation in Balb/c mice and specific pathogen free (SPF) chicken revealed that the efficacy of DNA vaccines could be boosted by co-administration of Freund's adjuvant and repeating DNA immunization. The vaccine trial in SPF chickens showed that both the circular and linearized plasmid DNA of pEGFP-N3IF produced significant levels of antibody against NDV after the second booster and conferred 40-47% protection upon lethal NOV challenge. Co-administration of the circular plasmids of pEGFP-N3/F and -NIIHN, produced antibodies efficiently and conferred more than 50% protection upon NOV challenge. The low and undetectable antibody level in some of the survivors suggests that DNA vaccine elicits cellular immune response in chicken. The overall results also suggest that both the F and HNDNA can be used as a vaccine component to provide effective protection against NDV and DNA immunization opens a new approach to the development of gene vaccine for chicken against infectious disease.